2016
DOI: 10.15252/embj.201694699
|View full text |Cite
|
Sign up to set email alerts
|

Codon identity regulates mRNA stability and translation efficiency during the maternal‐to‐zygotic transition

Abstract: Cellular transitions require dramatic changes in gene expression that are supported by regulated mRNA decay and new transcription. The maternal-to-zygotic transition is a conserved developmental progression during which thousands of maternal mRNAs are cleared by post-transcriptional mechanisms. Although some maternal mRNAs are targeted for degradation by microRNAs, this pathway does not fully explain mRNA clearance. We investigated how codon identity and translation affect mRNA stability during development and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

23
331
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 266 publications
(395 citation statements)
references
References 71 publications
23
331
0
1
Order By: Relevance
“…One example of this is codon-mediated stability control. Although a causal link from codon usage to mRNA half-life has been shown for a wide range of organisms (Hoekema et al 1987;Presnyak et al 2015;Bazzini et al 2016;Mishima and Tomari 2016), the underlying mechanism remains poorly understood. In S. cerevisiae, reporter gene experiments showed that codon-mediated stability control depends on the RNA helicase Dhh1 .…”
Section: Or In Thementioning
confidence: 99%
See 1 more Smart Citation
“…One example of this is codon-mediated stability control. Although a causal link from codon usage to mRNA half-life has been shown for a wide range of organisms (Hoekema et al 1987;Presnyak et al 2015;Bazzini et al 2016;Mishima and Tomari 2016), the underlying mechanism remains poorly understood. In S. cerevisiae, reporter gene experiments showed that codon-mediated stability control depends on the RNA helicase Dhh1 .…”
Section: Or In Thementioning
confidence: 99%
“…For instance, inserting strong secondary structure elements in the 5 ′ UTR or modifying the translation start codon context strongly destabilizes the long-lived PGK1 mRNA in S. cerevisiae (Muhlrad et al 1995;LaGrandeur and Parker 1999). Codon usage, which affects the translation elongation rate, also regulates mRNA stability (Hoekema et al 1987;Presnyak et al 2015;Bazzini et al 2016;Mishima and Tomari 2016). Further correlations between codon usage and mRNA stability have been reported in E. coli and S. pombe (Boël et al 2016;Harigaya and Parker 2016).…”
Section: Introductionmentioning
confidence: 96%
“…Strong coupling between poly(A) tail length and translation efficiency (TE) has been observed in the cleavage embryos of many species (Subtelny et al 2014;Eichhorn et al 2016;Lim et al 2016), although the molecular mechanisms that enable this coupling remain unclear. Recent studies have begun to determine a variety of mechanisms through which maternal mRNA clearance is accomplished (Giraldez et al 2006;Tadros et al 2007;Lund et al 2009;Tadros and Lipshitz 2009;Barckmann et al 2015;Bazzini et al 2016;Mishima and Tomari 2016). An important role has been ascribed to the evolutionarily conserved miRNA, miR-430/427, that mediates translational repression and clearance of a subset of maternal mRNAs in zebrafish and Xenopus embryos during MZT (Giraldez et al 2006;Lund et al 2009).…”
Section: [Supplemental Materials Is Available For This Article]mentioning
confidence: 99%
“…Moreover, specific sequence motifs that are recognized by trans-acting factors, such as microRNAs and RNA-binding proteins, often modulate mRNA stability by controlling translation initiation. This inverse relationship between translation initiation and degradation can be rationalized as the cap and poly(A) tail either being in a translationally competent mRNP or in an alternative nuclease accessible complex.Studies in organisms from E. coli to zebrafish now demonstrate that the "optimality" of an mRNA's codons modulates its stability [2][3][4][5]. The general theme is that "optimal" codons, which are recognized by abundant tRNAs and efficiently translated, are correlated with mRNA stability, whereas "non-optimal" codons, which are recognized by less abundant tRNAs, are correlated with mRNA instability.…”
mentioning
confidence: 99%
“…Studies in organisms from E. coli to zebrafish now demonstrate that the "optimality" of an mRNA's codons modulates its stability [2][3][4][5]. The general theme is that "optimal" codons, which are recognized by abundant tRNAs and efficiently translated, are correlated with mRNA stability, whereas "non-optimal" codons, which are recognized by less abundant tRNAs, are correlated with mRNA instability.…”
mentioning
confidence: 99%